'n Kwantitatiewe bepaling na die aard, omvang en gevolge van huishoudelike higiene in Botshabelo: Seksie M, met spesifieke verwysing na voedsel - van der Westhuizen, Yolandi (Bloemfontein: Central University of Technology, Free State, 1999)
Botshabelo, Section M in the Free State province is a typical disadvantaged third- world community, considering its infrastructure and socio-economic conditions. This study was conducted to assess the nature and extent offood hygiene in Section M of Botshabelo, in an attempt to identifY key areas concerning the health of the community and make recommendations with regard to these key areas. The study was conducted amongst a random sample of one hundred and twenty households that were selected from a map using the grid method. A structured questionnaire was compiled in both Afrikaans and Sesotho for obtaining infonnation from the mothers or children (older than 16 years) responsible for food preparation in the households. Infonnation with regards to infrastructure, personal hygiene, the occurrence of food-related diseases and other food hygiene related aspects were covered in the questionnaire. Two trained local community workers completed the questionnaires by means of interviewing. After encoding of the questionnaires they were processed by the Computer Centre of the University of the Orange Free State and analyzed by the Department of Biostatistics of the Orange Free State University. The study showed that basic facilities such as water, electricity and pitlatrines, provided to the area by the government and local authority, are available to the largest percentage of households. It appears that the residents of the area had good knowledge of personal hygiene and good household practices. However, if the high frequency of diarrhoea cases occurring in the area is kept in mind, doubt exists whether these practices are applied in the daily household routine. Results furthermore indicated that the source, appearance and quality are considered by residents when buying foodstuflS but do not weigh up to the strenuous socioeconomic conditions and geographical location, thus rendering price and availability the predominant considerations when buying foodstuflS. Three key areas that pose a definite health risk emanated from the study. These key areas need to be addressed as a fundamental step to elevate the health and welfure of the community. The key areas include: 1) the occurrence of diarrhoea 2) the eating of spoiled food and 3) the ignorance that exists with regard to the pasteurization of milk. If these key areas are addressed as part of community projects and awareness programmes in association with the residents, the health and welfare of the community can be improved radically. It is, in addition, essential that fmdings and recommendations concerning these key areas be made available to community leaders and health workers to drive these incentives.
Thesis
Keywords: Food handling - Health aspects - South Africa; Domestic hazards